Cleaning out the Litterbox of Proteomic Scientists’ Favorite Pet: Optimized Data Analysis Avoiding Trypsin Artifacts - Schittmayer, Matthias; Fritz, Katarina; Liesinger, Laura; Griss, Johannes; Birner-Gruenberger, Ruth (Journal of proteome research, 2016)
Chemically modified trypsin is a standard reagent in proteomics experiments but is usually not considered in database searches. Modification of trypsin is supposed to protect the protease against autolysis and the resulting loss of activity. Here, we show that modified trypsin is still subject to self-digestion, and, as a result, modified trypsin-derived peptides are present in standard digests. We depict that these peptides commonly lead to false-positive assignments even if native trypsin is considered in the database. Moreover, we present an easily implementable method to include modified trypsin in the database search with a minimal increase in search time and search space while efficiently avoiding these false-positive hits.